Ḍa. Māmaṇi Raẏachama Gosvāmīra sr̥shṭi āru anubhawa : Ḍa. Māmaṇi Raẏachama Gosvāmīra jīwana darśana āru sāhityarājira prati śraddhāñjali - Hājarikā, Anitā, 1963-; Asama Sāhitya Sabhā (Yorahāṭa : Asama Sāhitya Sabhā, 2013)
Contributed articles on the life and works of Mamani Rayachama Gosvami, Assamese author.
Includes bibliographical references.
In Assamese; includes passages in English.
Keywords: Goswāmī, Māmaṇi Raẏachama, -- 1942-2011 -- Criticism and interpretation; Goswāmī, Māmaṇi Raẏachama, -- 1942-2011.; Criticism, interpretation, etc